The Role of Auditing Practices that Affect Accounting Standards and Taxable Income: A Study in Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Taxable income is unsafe for the organization, as well as for the whole society. The writing uncovers that there is have to look at the viability of the auditing standard  set of principles. They likewise alluded to the part of bookkeeping principles in lessening the impact of taxable income. The reason for this study is to discover the relationship between auditing standard components and the record of asking gauges of expert bookkeepers. It pointed likewise to discover the relationship between bookkeeping models and assessable salary. The writing was assessed and broke down. Likewise, a structure was created. Ethical requirements, professional skepticism, professional judgment, sufficient, appropriate audit evidence and audit risk. Were the free variables of this study. Accounting standards and taxable income wage were the reliant variables. The information about  the study were gathered from 170 professional accountants  in iraq. Information examination was led utilizing SPSS. Numerous breaks down were performed. The discoveries demonstrated that the most imperative indicators of accounting standards are professional auditing took after by ethical requirements, professional skepticism, professional judgment, and sufficient appropriate audit evidence and audit risk. The accounting standards have an exceptionally negative impact on the taxable income. The study has given reasonable and hypothetical proposal to leaders and specialists.